Perak heritage mosques : evaluating the defects of building elements / Kartina Alauddin, Mohd Fisal Ishak and Muhammad Azim Muhamad Wazir - Kartina, Alauddin; Mohd Fisal, Ishak; Muhammad Azim, Muhamad Wazir (Universiti Teknologi MARA, Perak, 2018)
This research attempts to investigate the type of defects of heritage mosque. The aim of this research was to investigate the defects of building elements of heritage mosque in Perak. The observation method was used to evaluate the defects of building elements in heritage mosques. Data were presented as descriptive analysis with the evidence of pictures, table, and graph. The result concluded that there are cracks, peeling paint, fungus and missing/broken parts most defects in building elements of heritage mosques. In conclusion, this work would be able to assist the government or mosques administration in preparing maintaining strategy of heritage mosques.